2017
DOI: 10.1021/jacs.7b03300
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Active Sites for CO Reduction on Copper Nanoparticles; Suggestions for Optimizing Performance

Abstract: Recent experiments show that the grain boundaries (GBs) of copper nanoparticles (NPs) lead to an outstanding performance in reducing CO2 and CO to alcohol products. We report here multiscale simulations that simulate experimental synthesis conditions to predict the structure of a 10 nm Cu NP (158 555 atoms). To identify active sites, we first predict the CO binding at a large number of sites and select four exhibiting CO binding stronger than the (211) step surface. Then, we predict the formation energy of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(157 citation statements)
references
References 25 publications
7
150
0
Order By: Relevance
“…This stabilization is due to the electrostatic attraction between oppositely charged carbon atoms induced by the Cu + and Cu 0 interface, promoting C-C coupling 52 . We therefore concentrate on the Gibbs free energy of formation for COH* and OCCOH* as descriptors for methane formation and CO-CO dimerization to ethylene 53 . We began by constructing Cu(111) and Cu(211) slabs as model systems of flat and high-curvature Cu surfaces, respectively.…”
Section: Nature Catalysismentioning
confidence: 99%
“…This stabilization is due to the electrostatic attraction between oppositely charged carbon atoms induced by the Cu + and Cu 0 interface, promoting C-C coupling 52 . We therefore concentrate on the Gibbs free energy of formation for COH* and OCCOH* as descriptors for methane formation and CO-CO dimerization to ethylene 53 . We began by constructing Cu(111) and Cu(211) slabs as model systems of flat and high-curvature Cu surfaces, respectively.…”
Section: Nature Catalysismentioning
confidence: 99%
“…Numerous chemical modifications and nanostructuring approaches have led to improvements in product selectivity and catalytic activity. [17] Cheng et al also reported a theoretical study showing that highly active twin boundaries (TBs) on the Au surface can be superior to GBs and other defects for CO 2 RR. [2,12] Promotion of C2 products on Cu GBs has been predicted by Cheng et al, although in Li's studies the production of ethylene is low.…”
Section: Doi: 101002/adma201805405mentioning
confidence: 99%
“…[2,12] Promotion of C2 products on Cu GBs has been predicted by Cheng et al, although in Li's studies the production of ethylene is low. [17] Cheng et al also reported a theoretical study showing that highly active twin boundaries (TBs) on the Au surface can be superior to GBs and other defects for CO 2 RR. [18] Hence it would be interesting to realize Cu nanostructures with high TB for CO 2 RR.…”
mentioning
confidence: 99%
“…Thus, H 2 CO 3 decomposition likely follows a stepwise mechanism in bulk‐like water, but it might be different in other environments like an air/water interface. Goddard and coworkers have investigated multiple aspects of CO reduction on copper surfaces and copper nanoparticles with explicit water layers at different pH levels . Their studies of solvated systems were carried out using reactive force fields which significantly decrease the computational time required.…”
Section: Explicit Solvationmentioning
confidence: 99%